Long delays in identification and publication of naturalized species: a case study of introduced grasses in Hawai‘i - Kevin Faccenda; Curtis C. Daehler (NeoBiota)
As introduced plants spread across the world, botanists documented their naturalizations—self-sustaining reproduction in new geographic areas—through herbarium specimens and published reports, the primary sources for the study and management of biological invasions. Invasion lag time, attracting much attention from both theoretical and applied perspectives, is typically defined as the time between introduction and when a species starts to spread rapidly, which can be minimally estimated as the time between introduction and the first reported naturalization. Delays in identifying herbarium specimens and publication delays may inflate reported lag times, but such delays have rarely been quantified. The Hawaiian naturalized grass flora serves as a case study to examine these human-caused delays among 269 species. From herbarium data, we found the collection date of the first naturalized specimen, when it was correctly identified, and compared these to the publication date of the first naturalization report. The average delay was 27 years (a median of 17 years) between the first naturalized herbarium specimen and its publication, although this delay has decreased over time. Included in this delay is the time needed for correct identification of specimens, which averaged 18 years, but had a median of 4 years, indicating that most grasses are quickly identified but some required decades. These delays, when not accounted for, obscure temporal trends in invasions. It is also important to understand and account for these delays to better characterize the phenomena that contribute to reported lag times for biological invasions. Minimizing identification and publication delays in the future will be important for successful management and control of new invasions. Expanded investment in and support of taxonomic experts at biodiversity institutions is needed to reduce reporting delays for new naturalizations.